γ-Secretase Inhibitor Alleviates Acute Airway Inflammation of Allergic Asthma in Mice by Downregulating Th17 Cell Differentiation - Weixi Zhang; Xueya Zhang; Anqun Sheng; Cuiye Weng; Tingting Zhu; Wei Zhao; Changchong Li (Hindawi Limited, 2015)
T helper 17 (Th17) cells play an important role in the pathogenesis of allergic asthma. Th17 cell differentiation requires Notch signaling. γ-Secretase inhibitor (GSI) blocks Notch signaling; thus, it may be considered as a potential treatment for allergic asthma. The aim of this study was to evaluate the effect of GSI on Th17 cell differentiation in a mouse model of allergic asthma. OVA was used to induce mouse asthma model in the presence and absence of GSI. GSI ameliorated the development of OVA-induced asthma, including suppressing airway inflammation responses and reducing the severity of clinical signs. GSI also significantly suppressed Th17-cell responses in spleen and reduced IL-17 levels in serum. These findings suggest that GSI directly regulates Th17 responses through a Notch signaling-dependent pathway in mouse model of allergic asthma, supporting the notion that GSI is a potential therapeutic agent for the treatment of allergic asthma.